ANALISIS MOTIVASI BERWIRAUSAHA PADA GENERASI MILENIAL DI KOTA PONTIANAK - Ari Widiati; Fitriani , (Fakultas Ekonomi dan Bisnis Islam, 2021)
Entreprenuership is the most important part in economic develoment where is the right solution in overcoming unemployment and lack of employment or the employment opportunities. The younger generation (millenials generation) as the next generation of the nation must be able to create business opportunities so as not to increase the number of unemployment in the city of Pontianak. The millenials generation must have a dynamic and creative mindset in an effort to minimize the economic crisis and try to develop the entreprenuership in order to prosper the community. Hence, motivation is needed to support the course of one’s desires for entreprenuership both motivation from within ( intrinsic) or from outside (extrinsic). The aims of this study is to find out 1) intrinsic motivation and extrinsic motivation of millennial generation in running entreprenuership, 2) the obstacles faced by millennial generation in running the entreprenuership, and 3) millennial generation solution covercoming obstacles running the entrepreneurship. This qualitative study used a descriptive method where the data sources are divided into two; primary data and secordary data, while direct observation, in-depth interviews, and documentation are used as tools of data collecting. The data analysis techniques in this study are divided into four stages; data collection, reduction, presentation, and drawing conclusions or verification. To validity the data, the serearcer used checking technique through member check and triangulation. After conduting this study, it can be conclude that:1) milennial generation motivation in entrepreneurship is due to two factors, namely intrinsic factors which include the desire to succeed, the needs, the existence of future goals, the existence of business opportunities, good prospects of the community, and to meet the needs pf daily life. The second factor is the extrinsic motivition that can be obtained from the family and the closest people such as friends. 2) Entreprenuership is a good job and suitable for the millennial generation due to the advanced technology, so that they can be more creative and be able to innovate in accordance with the skills and hobbies of the millennial generation. 3) The constraints faced by these young entreprenuership vary according to the type of business, so the solutions needed also adjust to the type of business and place of business.